Practices and factors associated with active management of the third stage of labor in East Africa: systematic review and meta-analysis - Kelemu Abebe Gelaw; Yibeltal Assefa; Belete Birhan; Natnael Atnafu Gebeyehu (BMC, 2023)
Abstract Background Active management of the third stage of labor involves prophylactic uterotonics, early cord clamping, and controlled cord traction to deliver the placenta. It is designed to facilitate the delivery of the placenta by increasing uterine contractions during the third stage of labor. It is also used to prevent postpartum hemorrhage by averting uterine atony.This systematic review and meta-analysis's emphasis was on the practice and factors associated with active management of the third stage of labor in East Africa. Methods PubMed, Web of Science, Science Direct (Scopus), Google Scholar, African Journals Online, and the Cochrane Library electronic databases were used. Data were extracted using Microsoft Excel, and STATA version 14 was used for analysis. A p-value of 0.05 is regarded to indicate potential publication bias: the funnel plot, Begg, and Egger's regression test were used to examine publication bias. Using I2 statistics, the heterogeneity of the studies was evaluated. Pooled analysis was carried out. By country, a subgroup analysis was conducted. Results Thirteen studies were included in this systematic review and meta-analysis. The pooled prevalence of the practice of active management of the third stage of labor in East Africa was 34.42%. Received training (OR = 6.25, 95%CI = 3.69, 10.58), years of experience (OR = 3.66, 95%CI = 2.35, 5.71), and good knowledge (OR = 3.66, 95%CI = 2.35, 5.71) were statically associated with the practice of active management of third stage of labor. Conclusion The pooled prevalence of practice for active management of the third stage of labor in East Africa was low. Factors that were statistically associated with the practice were received training, years of experience, and good knowledge. Obstetric care providers should continue to receive training in all components of active management of the third stage of labor through training and education programs.